The roles of TRPV1, TRPA1 and TRPM8 channels in chemical and thermal sensitivity of the mouse oral mucosa - Kichko, Tetyana; Neuhuber, Winfried; Kobal, Gerd; Reeh, Peter (European Journal of Neuroscience, 2018)
Spices in food and beverages and compounds in tobacco smoke interact with sensory irritant receptors of the transient receptor potential (TRP) cation channel family. TRPV1 (vanilloid type 1), TRPA1 (ankyrin 1) and TRPM8 (melastatin 8) not only elicit action potential signaling through trigeminal nerves, eventually evoking pungent or cooling sensations, but by their calcium conductance they also stimulate the release of calcitonin gene-related peptide (CGRP). This is measured as an index of neuronal activation to elucidate the chemo- and thermosensory transduction in the isolated mouse buccal mucosa of wild types and pertinent knockouts. We found that the lipophilic capsaicin, mustard oil and menthol effectively get access to the nerve endings below the multilayered squamous epithelium, while cigarette smoke and its gaseous phase were weakly effective releasing CGRP. The hydrophilic nicotine was ineffective unless applied unprotonated in alkaline (pH9) solution, activating TRPA1 and TRPV1. Also, mustard oil activated both these irritant receptors in millimolar but only TRPA1 in micromolar concentrations; in combination (1 mm) with heat (45 °C), it showed supraadditive, that is heat sensitizing, effects in TRPV1 and TRPA1 knockouts, suggesting action on an unknown heat-activated channel and mustard oil receptor. Menthol caused little CGRP release by itself, but in subliminal concentration (2 mm), it enabled a robust cold response that was absent in TRPM8-/- but retained in TRPA1-/- and strongly reduced by TRPM8 inhibitors. In conclusion, all three relevant irritant receptors are functionally expressed in the oral mucosa and play their specific roles in inducing neurogenic inflammation and sensitization to heat and cold.
EVALuna2:35205